Post-activation performance enhancement of flywheel and traditional squats on vertical jump under individualized recovery time - Sun, Shaocheng; Yu, Ying; Niu, Yu; Ren, Meiling; Wang, Jiaoqin; Zhang, Ming (Frontiers in Physiology, 2024)
Purpose: To explore the post-activation performance enhancement (PAPE) of flywheel and traditional squats on a series of vertical jumps, and the loads of the two protocols were matched based on their linear velocities. In addition, we attempted to validate the effectiveness of determining individualized recovery time (IRT) between conditioning activities and explosive movements. Methods: Sixteen trained players participated in 3 main experiments. First, one-repetition maximum (1RM) assessment and intensity matching test. Second, weighted jump squat (WJS) test at baseline and at 2, 4, 6, 8, and 10 minutes after flywheel and traditional protocols. Third, squat jump (SJ), countermovement jump (CMJ), and approach jump (AJ) tests incorporating IRT determined in the WJS sessions into both protocols. These protocols were standardized to 8 repetitions at 80% 1RM with equivalent concentric speed matched by a linear position transducer and conducted in a random order on separate days. Results: In the WJS tests, both protocols exhibited significant increases on jump height (JH), peak force (PF), and peak power (PP) after 2 to 6 minutes (all p < 0.05), and the time courses of changes in performance were in a similar trend. In the SJ, CMJ, and AJ tests, both protocols demonstrated highly significant increases on JH, PP, and reactive strength index (RSI) after incorporating IRT (all p < 0.01), with all participants exhibiting diverse improvement above the baseline levels. The potentiation percentages of flywheel protocol on JH, PP and RSI were higher than traditional protocol across four jumping types (JH: 5.35-9.79% vs 4.13-8.46%; PP: 4.16-6.13% vs 3.23-4.77%; RSI: 7.27% vs 7.04%). Conclusion: High-intensity flywheel squats can produce jumping potentiation in neuromechanical factors comparable to, or even surpassing, those observed in traditional squats, potentially making them a more effective option for inducing PAPE. Additionally, incorporating IRT into potentiation protocols could further optimize the PAPE effects.